Protecting essential health services in low-income and middle-income countries and humanitarian settings while responding to the COVID-19 pandemic. Issue 10 (7th October 2020) - Blanchet, Karl; Alwan, Ala; Antoine, Caroline; Cros, Marion Jane; Feroz, Ferozuddin; Amsalu Guracha, Tseguaneh; Haaland, Oystein; Hailu, Alemayehu; Hangoma, Peter; Jamison, Dean; Memirie, Solomon Tessema; Miljeteig, Ingrid; et al.
Abstract : In health outcomes terms, the poorest countries stand to lose the most from these disruptions. In this paper, we make the case for a rational approach to public sector health spending and decision making during and in the early recovery phase of the COVID-19 pandemic. Based on ethics and equity principles, it is crucial to ensure that patients not infected by COVID-19 continue to get access to healthcare and that the services they need continue to be resourced. We present a list of 120 essential non-COVID-19 health interventions that were adapted from the model health benefit packages developed by the Disease Control Priorities project.